Cat admissions to RSPCA shelters in Queensland, Australia: description of cats and risk factors for euthanasia after entry. Issue 1 (21st January 2013) - Alberthsen, C; Rand, JS; Bennett, PC; Paterson, M; Lawrie, M; Morton, JM
<x xml:space="preserve">Abstract</x> Objective A lack of information limits understanding of the excess cat problem and development of effective management strategies. This study describes cats entering Royal Society for the Prevention of Cruelty to Animals (RSPCA) Queensland shelters and identifies risk factors for euthanasia. Methods Data for cats entering relevant shelters (July 2006–June 2008) were obtained from the RSPCA's electronic database. Univariable and multivariable logistic regression analyses were conducted to identify risk factors for euthanasia. Results Of 33, 736 cats admitted, 46% were adult cats (≥3 months) and 54% were kittens (<3 months). The most common reason for admission was stray (54%), followed by owner surrender (44%). Euthanasia was the most common outcome (65%), followed by adoption (30%). The odds of euthanasia were lower for kittens and for cats that were desexed prior to admission. Of the strays, 8% had been desexed. For cats of similar age, sex, desexed and feral status, stray cats were more likely to be adopted than owner‐surrenders. Conclusions Strategies are needed to reduce numbers of cats admitted and euthanased. Given the high proportion of admissions that were kittens, reducing the incidence of delayed sterilisation of owned cats may be an important strategy for reducing the number of unwanted kittens. Many cats admitted as strays were rehomable, but given the high proportion of admissions that are strays, further research on stray populations is needed. Future studies of cats entering shelters would be enhanced if data collection definitions, categories and methods were standardised.